Common genetic variants and subclinical atherosclerosis: The Multi-Ethnic Study of Atherosclerosis (MESA). (February 2016) - Vargas, Jose D.; Manichaikul, Ani; Wang, Xin-Qun; Rich, Stephen S.; Rotter, Jerome I.; Post, Wendy S.; Polak, Joseph F.; Budoff, Matthew J.; Bluemke, David A.
Abstract: Background and aims: Subclinical atherosclerosis (sCVD), measured by coronary artery calcium (CAC) and carotid intima media thickness (CIMT) is associated with cardiovascular disease (CVD). Genome-Wide Association Studies (GWAS) of sCVD and CVD have focused primarily on Caucasian populations. We hypothesized that these associations may differ in populations from distinct genetic backgrounds. Methods: The associations between sCVD and 66 single nucleotide polymorphisms (SNPs) from published GWAS of sCVD and CVD were tested in 8224 Multi-Ethnic Study of Atherosclerosis (MESA) and MESA Family participants [2329 Caucasians (EUA), 691 Chinese (CHN), 2482 African Americans (AFA), and 2012 Hispanic (HIS)] using an additive model adjusting for CVD risk factors, with SNP significance defined by a Bonferroni-corrected p < 7.6 × 10 −4 (0.05/66). Results: In EUA there were significant associations for CAC with SNPs in 9p21 (rs1333049, P = 2 × 10 −9 ; rs4977574, P = 4 × 10 −9 ), COL4A1 (rs9515203, P = 9 × 10 −6 ), and PHACTR1 (rs9349379, P = 4 × 10 −4 ). In HIS, CAC was associated with SNPs in 9p21 (rs1333049, P = 8 × 10 −5 ; rs4977574, P = 5 × 10 −5 ), APOA5 (rs964184, P = 2 × 10 −4 ), and ADAMTS7 (rs7173743, P = 4 × 10 −4 ). There were no associations between CAC and 9p21 SNPs for AFA and CHN. Fine mapping of the 9p21 region revealed SNPs with robust associations with CAC in EUA and HIS but no significant associations in AFA and CHN. Conclusion: Our results suggest some shared genetic architecture for sCVD across ethnic groups, while also underscoring the possibility of novel variants and/or pathways in risk of CVD in ethnically diverse populations. Highlights: Genetic studies of atherosclerosis have focused on Caucasian populations. Genetic associations were tested in the Multi-Ethnic Study of Atherosclerosis. There was replication of associations but also notable differences by ethnicity.